1972
DOI: 10.1139/v72-629
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals by Mass Spectrometry. XLV. Ionization Potentials and Heats of Formation of C3H3, C3H5, and C4H7 Radicals and Ions

Abstract: Using an energy-resolved electron beam, appearance potentials for C,H;, C,H:, and C4H: fragment ions from hydrocarbons of formula C3H4, C,H6, C4H6, C4H8, and C,Hlo have been measured. In each case the fragment appears to have a common structure, corresponding to AHr(C3H:) = 256 f 2 kcal/mol, AHr(C3H:) = 226 t 2 kcal/mol, and AHr(C4H:) = 206 + 2 kcal/mol. Ionization potentials have been measured for propargyl radical (8.68 V), methallyl radical (7.54V), and 2-methylallyl radical (7.89 V).Corresponding ionic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0
2

Year Published

1976
1976
1998
1998

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(53 citation statements)
references
References 28 publications
8
43
0
2
Order By: Relevance
“…It has been shown by experiment [9] and theory [10,11] that the aromatic cyclopropenyl cation and the aliphatic propagyl cation are the most stable C 3 H 3 isomers. Therefore, the dissociation pathways depicted in Scheme 3 are proposed for the loss of CO and CS from 3 a,b and 4 a,b, respectively, by which the corresponding C 3 H 3 CO and C 3 H 3 CS ions (3 c,d and 4 c,d, respectively) are formed.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown by experiment [9] and theory [10,11] that the aromatic cyclopropenyl cation and the aliphatic propagyl cation are the most stable C 3 H 3 isomers. Therefore, the dissociation pathways depicted in Scheme 3 are proposed for the loss of CO and CS from 3 a,b and 4 a,b, respectively, by which the corresponding C 3 H 3 CO and C 3 H 3 CS ions (3 c,d and 4 c,d, respectively) are formed.…”
Section: Resultsmentioning
confidence: 99%
“…It was a very broad signal of Gaussian shape, T0.,-640 meV. This reaction has its counterpart in the fragmentations of propene and cyclopropane' where the proposed reaction sequence was elimination of H2 followed by loss of H: For the C4Hs molecules the consecutive reactions can be either (l), then (7), or (2) followed by (8):…”
Section: Molecular Ion Fragmentationsmentioning
confidence: 94%
“…where at threshold, the daughter ion is known to have the ally1 structure. 8 The authors concluded that the effect of increasing the ionizing electron energy, namely a decrease in both 13C and *H randomization, could adequately be explained by a skeletal isomerization involving a series of 1,3 ring closures to form methylcyclopropane type ions. In contrast, however, they observed that molecular ions yielding C2 fragment ions apparently had undergone total carbon randomization prior to decomposition at all electron energies.…”
Section: Introductionmentioning
confidence: 99%
“…(5). The ionization energy of DMCP, 9.08eV (12), is below the photoenergy of the krypton (10.0eV) resonance radiation. The ionization efficiency for DMCP was determined at 123.6 nm and found to be q = 0.10.…”
Section: Introductionmentioning
confidence: 90%